Analisis faktor-faktor yang mempengaruhi keluarga untuk memberikan dukungan kepada klien diabetes mellitus Dalam menjalani diet - Amelia, Muharina -; Nurchayati, Sofiana -; Elita, Veny - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determine the factors that influence family for giving support to clients with diabetes mellitus in diet therapy. Methodology of this research was a descriptive correlative with cross sectional approach. The number of sample is 106 respondents who have diabetes mellitus at areas of Puskesmas Harapan Raya. The sample were taken proportionate stratified random sampling technique. The measurement tool of this research is questionnaires which consist of 32 quesionnaire of family support. This research used chi squre test as bivariate analysis and logistic regresision for multivariate analysis. The results of this research show there were relationship between the level of family knowledge (p value = 0,000 ), family practice (p value = 0,000), socio economic status (p value = 0,006) and compliance of diet therapy. The results also shows there are no relationship between the stage of family development (p value = 1,000), family emotion (p value = 1,000), spiritual (p value =0,302), socio cultural (p value = 0,621) and compliance of diet therapy. The result of test shows the highest factors to influence family to give support to client with diabetes mellitus in diet therapy is family knowledge with Exp(B) 65,985. It is suggested to health care providers of Puskesmas to involve family in nursing threatment of client with diabetes mellitus. Keywords : Diabetes mellitus, Diet, Family